LEXICAL FORMS AND MEANINGS OF REGISTER WORDS IN VALORANT GAME - Firdaus, Moh. Iqbal; Yudhawati, Haliza Tri (Universitas Muhammadiyah Tangerang, 2023)
This article presents a qualitative investigation into the types of Lexical Forms and meanings used in the online game Valorant, with a specific focus on how players employ different registers within the game's context. The study explores sociolinguistic theories related to register and online gaming, and employs qualitative methods to collect and analyze data from YouTube and Streaming videos. By examining the diverse linguistic practices of Valorant players, this research aims to shed light on the communicative strategies utilized in this gaming community.